Collective Health Nursing: the construction of critical thinking about the reality of health - Chaves, Maria Marta Nolasco; Larocca, Liliana Müller; Peres, Aida Maris (Revista da Escola de Enfermagem da USP, 2011)
This article presents an analysis of the Collective Health Nursing teaching-learning processes and research in view of the consolidation of the Brazilian National Health System (Sistema Único de Saúde - SUS), performed with the objective to acknowledge the potentiality of the health reality of the population as a strategy to approximate the field of nursing practice and training as a way to revert undesired health situations. Thus, the authors reflect about the work of Collective Health Nursing, as they understand it is a mediator to promoting teaching, learning and knowledge development in this field. The authors believe that those processes, founded on critical thinking, permit to reflect about the contradictions between the current public policy and the actions promoted by the sector, and, this way, contribute to overcome the current health care mode, which has historically been founded on curative actions towards individuals, to assuming a model that acknowledges the health needs and intervenes in the social determination of the health-disease process.